Identification of visual acuity in children who cannot read: bibliometric study (Research, Society and Development, 2022)
The identification of visual acuity in children who cannot read yet is the object of this study. The Programa Saúde na Escola (PSE) has as one of its objectives to assess the visual acuity (VA) of students. The bibliometric study allowed us to describe the characteristics of publications on visual acuity in children who cannot read, the resources and strategies employed to identify VA in these children , study objectives. We found 86 texts, 19 of which were selected. It was found in the literature that the most frequent age for visual acuity assessment is six years. The Snellen, Teller and RAD scales are resources for assessing the visual acuity of children who cannot read, with Snellen being the most used. Of these, the RAD stands out for being graduated in figures, being more suitable for children who do not know how to read. It was also noticed that the authors do not address the use of nursing diagnosis on visual acuity.